Pengaruh Salinitas Terhadap Pertumbuhan Dan Biomassa Semai Dan Kandungan Lipida Pohon Non-Sekresi Ceriops tagal - Ramayani Ramayani (Peronema Forestry Science Journal, 2012)
Effect of salinity on growth and biomass of seedlings and  lipid content at tree of non-secreter C. tagal was studied. The research was conducted in greenhouse, Faculty of Agriculture and Pharmaceutical research laboratory, Faculty of Pharmacy, University of Sumatra Utara from July 2011 to July 2012. The purpose of the research is to determine the level of growth and biomass C. tagal seedling at different levels of salinities, to analysis the lipid content in the leaves and roots of C. tagal at tree.The mangrove seedlings growing with varied salinities namely 0%, 0,5%, 1,5%, 2% and 3%, quatiplicate. Lipid extraction and analysis performed from leaves and roots of mature trees taken from the mangrove forest Pulau Sembilan, Langkat, North Sumatera.The results showed C. tagal seedling with different levels of salinities effected significantly height, diameter, and biomass. Growth of C. tagal seedling was best at 0,5% salinity with plant height (3,24 cm) and diameter(3,65 mm). Wet weight and dry weight of leaves, roots and stems of C. tagal seedlings had the highest at 1,5% salinity. Total lipids in the leaves and roots of C. tagal trees were of 16,2 mg and 8,9 mg. Key words: C. tagal seedlings, salinity, total lipid